Where elders cry, the young laugh: Proverbs 3:31–35 and the examining of malpractice in Nigeria - Uroko, Favour C. (Verbum et ecclesia, 2024)
This article examines Proverbs 3:31–35 in the exam malpractice crisis ravaging secondary schools in Nigeria. Proverbs 3:31–35 has the central thesis of the call to avoid the company of evildoers and the blessings of going on the right path. Scholars have approached the issue of examination malpractice from an economic, social and psychological lens. In this study, the Old Testament was used as the lens for tackling the situation. This is a qualitative study using the rhetorical method. The data were obtained from the Bible, Bible commentaries, gazettes, journal articles and other periodicals. Emerged themes include: (1) warning not to join bad people; (2) consequences of the warning and (3) end point of one’s decision. Exam misconduct reflects deeper societal concerns such as corruption, weak regulatory enforcement and the temptation to succeed at any cost.Intradisciplinary and/or interdisciplinary implicationsProverbs 3:31–35 has shown that the increasing number of graduates who cannot defend their certificates and corruption is caused by the blatant and obscene nature of exam malpractice in Nigeria. Old Testament and Practical Theology were implicated in the study.